Proceedings of the 7th International Scientific Conference Rural Development 2015 2015
DOI: 10.15544/rd.2015.027
|View full text |Cite
|
Sign up to set email alerts
|

Changes of Actinidia Kolomikta Fruit Texture During Storage in Controlled Atmosphere Chambers

Abstract: Investigations were carried out in 2013. A. kolomikta cv. ‘Laiba’, ‘Lankė’, ‘Landė’, ‘Paukštės Šakarva’ fruits were picked at the technical maturity stage. The amount of dry matter, soluble solids and texture parameters were established in fruits after harvesting and during storage. Fruits stored for 8 weeks in controlled atmosphere chambers with different air parameters (No. 1–21 % O2, No. 2–0.5 % O2, No. 3–1 % O2, No. 4–1 % O2 and 1 % CO2). Dry matter, soluble solids and texture analysis were done biweekly. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…The greatest amount of ascorbic acid was observed in ʽLandėʼ fruit. Our previous studies indicate that fruit of this cultivar usually accumulate larger amounts of ascorbic acid (Paulauskienė et al, 2015). Delgado and Sun (2000I indicated that amount of ascorbic acid in frozen fruit is most influenced by pre-freezing operations and freezing process basely has no significant effect on vitamin loss.…”
Section: Resultsmentioning
confidence: 77%
“…The greatest amount of ascorbic acid was observed in ʽLandėʼ fruit. Our previous studies indicate that fruit of this cultivar usually accumulate larger amounts of ascorbic acid (Paulauskienė et al, 2015). Delgado and Sun (2000I indicated that amount of ascorbic acid in frozen fruit is most influenced by pre-freezing operations and freezing process basely has no significant effect on vitamin loss.…”
Section: Resultsmentioning
confidence: 77%
“…(Leontowicz et al, 2016). In Lithuania, the cultivation of Actinidia kolomikta (Pranckietis et al, 2009;Česonienė et al, 2013;Paulauskienė et al, 2015) is developing intensively, while in Poland in recent years, the production of Actinidia arguta has been rapidly expanding (Kawecki, Bieniek, 2008;Latocha, 2008;2010;Bieniek, 2013). As results from the research and field experiments concerning morphological, physiological and phenological features in the conditions of growth, pollination, cultivation and storage of hardy kiwifruit carried out so far in Europe, this plant has good prospects for development (Cossio et al, 2015).…”
Section: Introductionmentioning
confidence: 99%